A review of the development divide between Global North and South through a Foucauldian perspective: The divide: a brief guide to global inequality and its solutions, by J. Hickel, London, William Heinemann, 2017, £23.66 (hardcover), ISBN: 9781785151125. Issue 1 (31st December 2022) - Rambaldi, Chiara
ABSTRACT: 'Unequal development': a cherry narrative always assumed as natural and continuous between the Global North and South. As de facto assumed, the foundation of poverty has always been diagnosed as a domestic and technical immaturity of developing countries that will find a solution within the international economic order. But what if the North–South divide was the direct product of a political palette nurtured by the supposed solution to the problem? In his book The Divide: A Brief Guide to Global Inequality and its Solutions, Jason Hickel turns his back on old developmentalist formulas, challenging the development-machine effectiveness based on foreign intervention and international institutions' agendas. The author, anthropologist at the London School of Economics, analyses through historical fragments the core of an economic order built over centuries to benefit a small percentage of mankind in the name of progress. Accordingly, his analysis proves eliminating inequality and poverty would mean unsettling the world economic system the international arena is based on. The answer? Eventually, the acceptance of a new economic order willing to embrace debts liberation, more democratic and participatory agencies, and a biased trading system to favor developing nations.